21 hours ago · Sure! Let's solve the equation \(√(6x - 2) = √(4x + 4)\ step by step: 1. Remove the Square Roots: We can start by squaring both sides of the equation to ...

21 hours ago · Solve the square root equation 2 √(x) = √(x+6) .A. x = 6. B. x = 2. C. x = (\pi)/(5) D. x = -6. 1. See answer. plus. Add answer+5 pts.

Rating

(203)

21 hours ago · The gravitational force formula is mc001-1.jpg where F is the force between two objects, G is the constant of gravitation, m1 is the mass of the first object.

21 hours ago · Question: Solve the radical equation. Check all proposed solutions.\[\sqrt{x+6}=x-6\]Select the correct choice below and, if necessary, fill in the answer ...

16 hours ago · If sqrt(x^2 + y^2)= e^t & t = sin–1(y/sqrt(x^2+y^2)), then, dy/dx is equal ... (6x.sqrt(x)/1-9x^3) is x . g(x), then g(x) equals #maths. Ankit Kumar · 3:27 ...

21 hours ago · Free Online Scientific Notation Calculator. Solve advanced problems in Physics, Mathematics and Engineering. Math Expression Renderer, Plots, Unit Converter ...

20 hours ago · I believe factoring the difference of squares, x^2-64=(x+8)(x-8) is better to understand the existence of two solution of 8 and -8.

Rating

(30)

7 hours ago · If x=6 is the only x-intercept of the graph of a quadratic equation, which statement best describes the discriminant of the equation? The discriminant is 0.

17 hours ago · I am trying to fully understand the math behind conic sections. In particular, I am trying to go from the general equation for a hyperbola ((x-h)²/a²…